Unlocking the Vault of Privilege: How Trust Funds Perpetuate Wealth, Education Gaps, and Social Inequality Across Generations - Indra Lukmana Putra; Annisa Fatimah; Alie Zainal Abidin; Ascosenda Ika Rizqi (Center for Indonesian Accounting Studies, 2026)
Research Objective - Trust fund families preserve and transfer wealth across generations, and the implications of inherited capital for educational opportunities, socioeconomic mobility, and persistent social inequality are examined. These mechanisms reinforce the cumulative advantages of affluent families. Method: A qualitative approach using a systematic literature review of recent empirical studies on intergenerational wealth transfer, family socioeconomic status, educational attainment, and social mobility. Relevant peer-reviewed articles were analyzed for thematic content to identify recurring patterns and conceptual relationships. The synthesized findings were used to develop an integrated framework explaining the socioeconomic role of trust-fund families. Findings: Trust fund families utilize inherited financial assets to maintain long-term economic security and reduce exposure to labor market uncertainty. Wealth transferred through trust funds provides beneficiaries with greater educational opportunities, improved access to elite institutions, and enhanced social mobility compared with families lacking comparable financial resources. differences in individual academic performance, thereby reinforcing cumulative socioeconomic advantages across generations Theoretical and Policy Implications - Intergenerational wealth transmission by positioning trust funds as institutional mechanisms that facilitate socioeconomic privilege. Policymakers should consider taxation, inheritance, and educational equity policies that reduce opportunity disparities while promoting more inclusive social mobility. Research Novelty - Integrated conceptual framework linking trust fund governance, intergenerational wealth preservation, educational advantage, and cumulative social inequality.